2023
DOI: 10.3389/fsurg.2023.966971
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and treatment strategies of aggressive angiomyxoma in women: A retrospective review of 87 cases

Abstract: ObjectiveAggressive angiomyxoma (AAM) is a rare kind of soft tissue tumor. The purpose of this study is to summarize the clinical manifestations and treatment strategy of AAM in women.MethodWe searched the case reports on AAM in EMBASE, Web of Science and PubMed, China biomedical database, Wanfang database, VIP database, and China National Knowledge Internet from the start of database construction to November 2022 without any language restrictions in place. Then, the obtained case data were extracted, summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…13 Nevertheless, local recurrence of angiomyxoma after local postoperative radiotherapy was noted in a literature review. 14 Considering the two recurrences of the lesion in the present case, we recommended postoperative radiotherapy to prevent further recurrences; however, this was not performed because the patient declined.…”
Section: Discussionmentioning
confidence: 89%
“…13 Nevertheless, local recurrence of angiomyxoma after local postoperative radiotherapy was noted in a literature review. 14 Considering the two recurrences of the lesion in the present case, we recommended postoperative radiotherapy to prevent further recurrences; however, this was not performed because the patient declined.…”
Section: Discussionmentioning
confidence: 89%
“…In their study, none of the 24 patients who underwent CT examinations were diagnosed with AA. 9 Despite this finding, the importance of relying on various imaging modalities in assessing the tumor spread into surrounding tissues cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…AA generally have a locally invasive and infiltrating growth pattern in the surrounding tissues. 7 , 9 Some sources describe their behavior as displacing adjacent organs rather than truly invading them. 8 However, in our patient, the mass was well-defined and limited to the superficial soft tissue, which is unusual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging features of alternating hypointense bands forming layered patterns on T2 weight (T2W) were observed in 83% of cases [ 6 ]. A literature review by Wang and colleagues found that only 7 out of 65 AAM patients were accurately diagnosed initially, accounting for 10.77% of cases [ 7 ]. However, by combining factors of epidemiology, clinical progression, and tumor characteristics on image findings, diagnosing AAM pretreatment is not unachievable.…”
Section: Introductionmentioning
confidence: 99%